2020
DOI: 10.1038/s41420-020-00308-9
|View full text |Cite|
|
Sign up to set email alerts
|

Early-life stress induces EAAC1 expression reduction and attention-deficit and depressive behaviors in adolescent rats

Abstract: Neonatal maternal separation (NMS), as an early-life stress (ELS), is a risk factor to develop emotional disorders. However, the exact mechanisms remain to be defined. In the present study, we investigated the mechanisms involved in developing emotional disorders caused by NMS. First, we confirmed that NMS provoked impulsive behavior, orienting and nonselective attention-deficit, abnormal grooming, and depressive-like behaviors in adolescence. Excitatory amino acid carrier 1 (EAAC1) is an excitatory amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…There is also evidence suggesting that ELA, specifically MS, may have a delayed impact on PV cell density. Brains that were collected immediately (or within a few days) after ELA experience generally had no significant differences in PV levels compared to control-rearing (Giachino et al, 2007 ; Brenhouse and Andersen, 2011 ; Soares et al, 2020 ; Richardson et al, 2021 ), while brains collected later in life (in adolescence and/or P40 and older) generally had decreased PV levels (Leussis et al, 2012 ; Wieck et al, 2013 ; Ganguly et al, 2015 ; Lukkes et al, 2017 , 2018 ; Kim et al, 2020 ; Aksic et al, 2021 ). Since PV cells have been found to increase significantly in number from juvenility to adolescence in brain regions such as the PFC (Caballero et al, 2014 ; Wu et al, 2014 ), it is possible that ELA may inhibit the maturational time course of PV cells.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence suggesting that ELA, specifically MS, may have a delayed impact on PV cell density. Brains that were collected immediately (or within a few days) after ELA experience generally had no significant differences in PV levels compared to control-rearing (Giachino et al, 2007 ; Brenhouse and Andersen, 2011 ; Soares et al, 2020 ; Richardson et al, 2021 ), while brains collected later in life (in adolescence and/or P40 and older) generally had decreased PV levels (Leussis et al, 2012 ; Wieck et al, 2013 ; Ganguly et al, 2015 ; Lukkes et al, 2017 , 2018 ; Kim et al, 2020 ; Aksic et al, 2021 ). Since PV cells have been found to increase significantly in number from juvenility to adolescence in brain regions such as the PFC (Caballero et al, 2014 ; Wu et al, 2014 ), it is possible that ELA may inhibit the maturational time course of PV cells.…”
Section: Introductionmentioning
confidence: 99%
“…Findings of decreased PV cell numbers in CA1, CA2, CA4, and the parasubiculum in individual studies have been countered by findings of no change in PV cell numbers across hippocampal subregions ( Chu et al., 2016 ; Knable et al., 2004 ; Pantazopoulos et al., 2010 ; Wang et al., 2011 ). The entorhinal cortex, despite one null report ( Kim et al., 2020 ), had lower PV cell density in two studies ( Pantazopoulos et al., 2010 ; Wang et al., 2011 ). Individual studies have examined BA24 and the thalamic reticular nucleus (TRN) of BD patients and found increased clustering but unchanged density of PV cells in BA24 ( Cotter et al., 2002 ) and decreased total PV cell number in the TRN of BD patients ( Steullet et al., 2018 ).…”
Section: Resultsmentioning
confidence: 79%
“…There was little evidence of changes in mRNA or protein in the whole hippocampus ( Banasr et al., 2017 ; Bath et al., 2016 ; Brenhouse and Andersen, 2011 ; Kim et al., 2020 ; Lussier and Stevens, 2016 ; Rossetti et al., 2018 ; Ueno et al., 2018 ) or in its subregions ( Clarke et al., 2019 ; Krugers et al., 1996 ; Nowak et al., 2010 ; Soares et al., 2020 ) and the studies showing an effect reported mixed directionality ( Bath et al., 2016 ; Kim et al., 2020 ; Lussier and Stevens, 2016 ; Riga et al., 2017 ; Rossetti et al., 2018 ; Ueno et al., 2017 ). The few studies including enrichment paradigms showed contradictory effects ( Donato et al., 2013 ; Gomes da Silva et al., 2010 ; Kong et al., 2017 ; McHugh et al., 2009 ; Prévot and Sibille, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations